Genetic implication of Shorea johorensis Foxw propagation methods in selective cutting and line planting silvicultural system - ISKANDAR ZULKARNAEN SIREGAR; TEDI YUNANTO; PRIJANTO PAMOENGKAS (Biodiversitas Journal of Biological Diversity, 2008)
Attempt to rehabilitate degraded natural forests in Indonesia is recently carried out by applying selective cutting and line planting (TPTJ) silvicultural system. One of the most important aspects of TPTJ silvicultural system is the procurement methods of large number of planting stocks. Shorea johorensis Foxw was investigated in this regards as one of promising Shorea species for rehabilitating degraded forests due to its fast growing character. The species is usually propagated by three different propagation techniques, namely up-rooted seedlings, seeds and cuttings. Genetic consequences due to different propagation methods in this species are poorly known and need to be studied in order to determine genetic variation and differentiation. Material from five origins (populations), namely: (i) up-rooted seedlings, (ii) seeds, (iii) cuttings, (iv) young plantation and (v) natural forest were randomly taken in the field and subsequently assessed by RAPD using threepreviously tested random primers of OPO-11, OPO-13 and OPO-16. Results showed that natural tree populations showed the highest levels of genetic variation with mean values na = 1.2593, ne = 1.2070, PLP = 25.93% and He = 0.1109. Cutting populations showed the lowest levels of genetic variation with mean values na = 1.1111, ne = 1.0773, PLP = 11.11% and He = 0.0445. Meanwhile, according to the propagation techniques, up-rooted seedling population revealed the highest levels of genetic variation with mean values na = 1.2222, ne =1.1613, PLP = 22.22% and He = 0.0886. Particular methods of plant propagation in this company, especially cutting method, reduced significant genetic variation of S. johorensis.Key words: Shorea johorensis Foxw, RAPD, genetic variation, silvicultural system